Investigation on the Urban Grey Water Treatment Using a Cost-Effective Solar Distillation Still - Yusof M.F.; Zainol M.R.R.M.A.; Riahi A.; Zakaria N.A.; Shaharuddin S.; Juiani S.F.; Noor N.M.; Zawawi M.H.; Ikhsan J. (MDPI, 2023)
Treating urban grey water with physical, chemical, and biological treatment techniques and reusing it as a sustainable non-potable water source has received much attention recently, yet there is a lack of studies regarding it. In this work, a typical slum nearby an urban household area in Malaysia was selected as a source of contaminated grey water which is located on the opposite side of a building site (10029? E and 57? N) located in an urban area in a city in the Perak state, namely Parit Buntar, where the total urban grey water was being accumulated. Poor sanitation of that slum was seen to pose various health risks to the public, and hence, the importance of treating its grey water was perceived. Thus, this study was conducted to evaluate the performance of a low-cost double slope passive solar still by treating the grey water from the aforementioned slum, as well as to analyze the quality, quantity, and cost per liter of the produced water. Grey water was collected and filled in the solar still basin at s depth of 1 cm. The cover and basin of the solar still were made from transparent polythene film and black-painted stainless steel trough, respectively, while the frame was made from polyvinyl chloride (PVC), and the solar still was named PSSG1 abbreviated. PSSG1 was exposed to Malaysias climate conditions for several days from 8.00 a.m. to 6.00 p.m. at Universiti Sains Malaysia (USM), which was able to produce the maximum amount of water up to 4.11 L/m2d with the cost per liter/m2 of only USD 0.0082. Water quality parameters tested showed that water produced from PSSG1 met the standards of the restricted and unrestricted reusable non-potable grey water, the World Health Organization (WHO), and the Malaysian class I drinking water standards. It was also found that the PSSG1 with higher average daily basin water temperature produced water with higher quality for the reuse applications and yielded healthier water compared to the water produced by some reported previous grey water treatment techniques. Therefore, the cost-effective PSSG1 can be used as a daily practical alternative for treating low-strength grey water collected from various urban household areas in Malaysia in order to assist pollutants removal from the drained urban grey waters. 2022 by the authors.